Electrochemical DNA sensor for label-free soybean transgenic detection - Tam, Phuong Dinh; Binh, Nguyen Hai; Tuan, Mai Anh; Chien, Nguyen Duc (Vietnam Journal of Chemistry, 2014)
This paper describes the development of electrochemical label- free DNA sensor for detection of transgenic in Round–up Ready Soybean (herbicide tolerance). Two pairs of electrodes which the optimized dimension is 70µm x 30µm (the width of electrode x inter-distance between fingers), were fabricated on a chip for differential measures. The DNA probe (35S 5’-GCT CCT ACA AAT GCC ATC A-3) was designed in such a way that it can hybridize with the CaMV 35S promoter of Roundup Ready soybean. The DNA was immobilized on the surface of the sensor by the mean of (3-aminopropyl)triethoxysilane (APTS) polymer. The response time of DNA sensor is less than 1 second; in case of 100% matching level, the sensitivity is 2 mV/µM. The activity of DNA sensor remains unchanged after 9 months of storage at -4oC in DI water. Some random soybean samples were collected, extracted and tested by the DNA sensor and the results were well matched with the of PCR method.